Development of Prosocial Behavior through Music Classroom in Non-formal Private School - Panthongsem, Warodsamon; Udtaisuk, Dneya (An Online Journal of Education, 2021)
The purpose of this research was to identify guidelines for the development of prosocial behaviors in students in music classrooms in non-formal private schools. The key informants were music teachers and top-level management in non-formal private schools which specialize in teaching music. The data collecting method consisted of: 1) questionnaire, and 2) interview form. The research results indicated that: 1) Music teachers can develop prosocial behaviors in their students by using positive reinforcement as well as by acting as a good role model; 2) Having advanced psychological skill in teaching music is the most challenging issue for developing prosocial behaviors in private lessons; 3) The most desirable prosocial behavior that music teachers hoped to see was that students would use music knowledge for betterment of society; and 4) Prosocial behavior development guidelines should be aligned with the curricula in 5 core aspects. These aspects are (1) Teaching Content, which is music knowledge; (2) Teaching Objective, which is teaching music and developing prosocial behaviors at the same time; (3) Lesson Plan, which must be personalized in order to fully understand and meet students’ individual needs; (4) Academic In-class Activities, which aim to provide practical and hands-on experiences for students; and (5) Learner Experience Out-of-the-class Activities, which are created by teachers in order to encourage students to learn to peacefully coexist with others.